(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Fuzzy sets with intuitionistic properties are a more advanced record of thetraditional fuzzy set, which is frequently used in a variety of applications to deal withuncertainty and fuzzy situations. In general, similaritydistance measures are an important tool fordistinguishing between two sets, and they can also be used to solve pattern recognitiondifficulties. Despite the fact that different similarity measures have already been proposed, there isstill a lot of room for improvement because some of them fail to satisfy the characteristics ofsimilarity measures and produce inconsistent findings. We proposed new similarity measures inthis research that may contrast picture Fuzzy Sets. In this study, we attempt to perform patternrecognition on PFSs using the provided similarity measures.